The Dynamics Of Arabic Curriculum Management: Concepts, Characteristics, And Study Area - Achmad Diny Hidayatullah (Sean Institute, 2024)
This study delves into the landscape of Arabic curriculum management by examining its core concepts, characteristics, and study area. Curriculum management within Arabic language education is pivotal for aligning instructional practices with educational objectives, particularly in a context where linguistic and cultural precision are crucial. The study elucidates the conceptual framework of Arabic curriculum management, emphasizing the strategic selection and organization of content that resonates with the linguistic needs of learners. In this study, the researcher used a qualitative method. The approach used by the researcher is library research. Data from journals and books on Arabic curriculum management were collected, and then discussed. The research data is presented in three domains: concepts, characteristics, and the area of study of Arabic curriculum management. Research data found that the curriculum's relevance in addressing contemporary societal needs and its role in fostering practical communication skills among learners. The scope of the study is expansive, covering the development of teaching materials, innovative instructional strategies, and comprehensive assessment methodologies. This study also investigates how these components interact to enhance educational outcomes, improve teacher performance, and contribute to the overall success of Arabic language programs. By offering a detailed analysis of these elements, the study provides valuable insights into the effective management of Arabic curricula, ensuring that they meet the evolving demands of both learners and the global Arabic-speaking community.